![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3. ( 3 x - 9 ) = 81
3 x - 9 = 81 : 3
3 x - 9 = 27
3 x = 27 + 9
3 x = 36
x = 36 : 3
x = 12
[( 6 x - 32 ) : 2 + 56 ] . 14 = 2814
( 6 x - 32 ) : 2 + 56 = 2814 : 14
( 6 x - 32 ) : 2 = 201 - 56
6 x - 32 = 145. 2
6 x = 290 + 32
x = 322 : 6
dư nha bạn
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
x 8 = − 1 4 x .4 = − 1.8 x .4 = − 8 x = − 2
b)
6 x − 3 = 9 2 x − 7 6. 2 x − 7 = 9. x − 3 12 x − 42 = 9 x − 27 3 x = 15 x = 5
c)
x − 1 2 2 = 4 x − 1 2 = ± 2
TH1:
x − 1 2 = 2 x = 5 2
TH2:
x − 1 2 = − 2 x = − 3 2
Vậy x = 5 2 hoặc x = − 3 2
![](https://rs.olm.vn/images/avt/0.png?1311)
a)4.(x+3)-(2x-12)=x-(-11+4)
4x+12-2x+12=x+11-4
2x+24=x+7
2x-x=-24+7
x=-17
b)-(4x-13)+(5x-4)=-3-(-15+7)
-4x+13+5x-4=-3+15-7
(-4x+5x)+13-4=12-7
x+9=5
x=-4
c)(5x-3)-(-2x+4)=6x-12
5x-3+2x-4=6x-12
5x+2x-6x=3+4-12
x=-5
d)(15x+20)-(9x-3)=5x-(-12)
15x+20-9x+3=5x+12
15x-9x-5x=-20-3+12
x=-11
e,(7x+14)+(3x-8)=-(-9x+3)
7x+14+3x-8=9x-3
7x+3x-9x=-14+8-3
x=-9
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1.\left(x-2\right).\left(x+14\right)=0\)
<=>\(\orbr{\begin{cases}x-2=0\\x+14=0\end{cases}}\)
<=>\(\orbr{\begin{cases}x=2\\x=-14\end{cases}}\)
\(2.\left(x-2\right).\left(x+4\right)=0\)
<=>\(\orbr{\begin{cases}x-2=0\\x+4=0\end{cases}}\)
<=>\(\orbr{\begin{cases}x=2\\x=-4\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
7/48 - (1/2 x 2 + 1/6 x 4 + 1/8 x 5 + 1/12 x 7 + 1/14 x 8) : x = 0
7/48 - (1 + 2/3 + 5/8 + 7/12 + 4/7) : x = 0 (đã rút gọn)
7/48 - (336/336 + 224/336 + 210/336 + 196/336 + 192/336) : x = 0 (quy đồng)
7/48 - 193/56 : x = 0
193/56 : x = 0 + 7/48
193/56 : x = 7/48
x = 193/56 : 7/48
x = 1158/49
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(6x-3^4\right).7^{13}=3.7^{14}\)
\(\left(6x-3^4\right).7^{13}=3.7.7^{13}\)
\(\Rightarrow6x-81=21\)
\(\Rightarrow6x=102\)
\(\Rightarrow x=17\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) 8x - 6x - 15 = 13
2x = 13 + 15
2x = 28
x = 28 / 2 => x = 14
b) 19 + 25 = x + x + 2x -4
19 + 25 + 4 = 4x
48 = 4x
=> x = 48/4 = 12
c ) 49 - 14 = 6x - x + 5
49 - 14 -5 = 5x
30 = 5x
x = 30/5
=> x = 6
8x - 6x - 15 = 13
=> 2x = 28
=> x = 14
19 + 25 = x + x + 2x - 4
=> 44 = 4x - 4
=> 44 + 4 = 4x
=> 48 = 4x
=> x = 12
49 - 14 = 6x - x + 5
=> 35 = 5x + 5
=> 5x = 30
=> x = 6
![](https://rs.olm.vn/images/avt/0.png?1311)
a)13-2(x+1)=7
2.(x+1)=13-7
2.(x+1)=6
x+1=6/2
x+1=3
x=3-1
x=2
a, 13 - 2 ( x + 1 ) = 7
2 .( x + 1 ) = 13 - 7
2 .( x + 1 ) = 6
x + 1 = 6 : 2
x + 1 = 3
x = 3 - 1
x = 4
\(6x\left(x-4\right)=\dfrac{14}{3}\Leftrightarrow6x^2-24x-\dfrac{14}{3}=0\Leftrightarrow x=\dfrac{6\pm\sqrt{43}}{3}\)